Nanomaterial-based gas sensors: A review. Issue 2 (4th March 2018) - Xu, Ke; Fu, Chuhan; Gao, Zhijun; Wei, Fanan; Ying, Yu; Xu, Chong; Fu, Guojiang
ABSTRACT: The detection of gas molecules is critical for environmental monitoring, chemical process control, agriculture, and medical applications. Therefore, gas sensors and electronic noses (e-nose) are widely studied by researchers all over the world. Graphene has been considered to be a promising gas detection material due to its special electronic properties, which are strongly influenced by the adsorption of extrinsic molecules. Doping of metal oxides and nanometal particles has also been extensively studied and their electrical property is highly sensitive to the properties of absorbed gases. Carbon nanotubes (CNTs) are expensive but have advantages of high sensitivity, good reversibility, and nice stability. Several research groups have studied the mixed structure of the above three materials with their derivatives blended, which show improved gas sensing capabilities. This review summarizes the state-of-the-art progresses in the research on gas sensors and e-nose, based on graphene, metal oxide, and CNTs.